2022
DOI: 10.3390/ani12151954
|View full text |Cite
|
Sign up to set email alerts
|

KAT2B Gene Polymorphisms Are Associated with Body Measure Traits in Four Chinese Cattle Breeds

Abstract: Identifying molecular markers related to growth characteristics or meat quality is significant for improving beef cattle breeds. K(lysine) acetyltransferase 2B (KAT2B) is a transcriptional co-activator regulating the acetylation modification of histones, which may be involved in the development and metabolism of muscle and adipose. However, investigations of KAT2B genetic variations in Chinese native cattle are still limited. This study aimed to identify crucial single nucleotide polymorphisms (SNPs) influenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…This study primarily focused on the association between mutations at the InDel locus and the morphometric traits in three sheep breeds; the traits varied within the breeds. These results might result from the differences in the genetic backgrounds of the different breeds [30]. Wang et al [9] observed three genotypes (II, ID, and DD) at ten novel InDels of FTO in Tong sheep, which were similar to those of this study.…”
Section: Discussionsupporting
confidence: 86%
“…This study primarily focused on the association between mutations at the InDel locus and the morphometric traits in three sheep breeds; the traits varied within the breeds. These results might result from the differences in the genetic backgrounds of the different breeds [30]. Wang et al [9] observed three genotypes (II, ID, and DD) at ten novel InDels of FTO in Tong sheep, which were similar to those of this study.…”
Section: Discussionsupporting
confidence: 86%